2009
DOI: 10.1097/rct.0b013e31817c6b33
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector Computed Tomography Coronary Angiography

Abstract: Multidetector computed tomography has been progressively used for evaluation of coronary artery disease, so the knowledge about the anatomy of coronary arteries and veins is of fundamental importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…of patients Use of β-blockers (%) HR° (bpm) SNG dose (mg) Time between SNG and scan (minutes) Diameter Evaluable segments Image quality Physiological Diagnostic accuracy Dewey, 2006 [ 17 ] 16 and 64-slice Intra-individual 10 0 69 1.2 ? Kang, 2007 [ 18 ] + 16-slice Retrospective 81 0 66 0.6 <5 Chun, 2008 [ 19 ] 16-slice Retrospective 76 80 61 0.6 # 1 Decramer, 2008 [ 20 ] 64-slice Randomized 42 ^ 57 0.4 5 Zhang, 2008 [ 21 ] 64-slice Retrospective 90 47 59 0.4 1 Klass, 2009 [ 22 ] 40-slice Retrospective matched 60 ^^ ? 0.8 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…of patients Use of β-blockers (%) HR° (bpm) SNG dose (mg) Time between SNG and scan (minutes) Diameter Evaluable segments Image quality Physiological Diagnostic accuracy Dewey, 2006 [ 17 ] 16 and 64-slice Intra-individual 10 0 69 1.2 ? Kang, 2007 [ 18 ] + 16-slice Retrospective 81 0 66 0.6 <5 Chun, 2008 [ 19 ] 16-slice Retrospective 76 80 61 0.6 # 1 Decramer, 2008 [ 20 ] 64-slice Randomized 42 ^ 57 0.4 5 Zhang, 2008 [ 21 ] 64-slice Retrospective 90 47 59 0.4 1 Klass, 2009 [ 22 ] 40-slice Retrospective matched 60 ^^ ? 0.8 …”
Section: Resultsmentioning
confidence: 99%
“…Seven studies evaluated the effect of sublingual nitroglycerin on coronary diameter on CCTA. Two studies used a randomized design [ 20 , 23 ], one used intra-individual comparison [ 17 , 25 ], one used a matched design [ 22 ] and two used a retrospective review of their database [ 18 , 24 ]. All studies demonstrated an overall increase in diameter with the use of nitroglycerin, ranging from 8 to 30 % (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations